Sources and Behavior of Particulate Organic Carbon in the Yellow Sea and the East China Sea Based on 13C, 14C, and 234Th - Seo, Junhyeong; Kim, Guebuem; Hwang, Jeomshik (Frontiers in Marine Science, 2022)
The cycling of particulate organic carbon (POC) in continental shelf regions of the Yellow Sea (YS) and the East China Sea (ECS) was investigated by analyzing the concentrations and carbon isotope signatures (δ13C, Δ14C) of POC, together with the particulate aluminum (Al) concentration and 234Th activity over the period 10–20 August 2020. POC concentrations in the surface layer (0–20 m) were twice as high as those in the middle layer (20–50 m); the highest concentrations of all were observed in the bottom layer (> 50 m) of the YS and the region affected by Changjiang Diluted Water (CDW). Particulate Al concentrations in the bottom layer were three times higher than those in the overlying water column, indicating extensive sediment resuspension. Based on the three-endmember mixing model for the dual carbon isotopes, the estimated contribution of resuspended sedimentary organic carbon to POC ranged from 18% in the surface layer to 65% in the bottom layer. The contribution of riverine input to POC ranged from < 5% in the CDW region to ∼45% in the surface layer of the YS region, whereas that of in situ production was ∼40% in the entire study region. A deficiency of 234Th relative to 238U indicates short residence times of particles in the entire water column (2.6 ± 2.2 d). The flux of POC settling to the seafloor, calculated based on 234Th–238U disequilibrium, was 47–125 mmol m–2 d–1. The POC settling flux was one to two orders of magnitude higher than the burial rate of POC in the underlying sediment, implying the rapid decomposition of POC before incorporation into the sediment. Thus, sediment resuspension is prevalent and an important component of the POC cycling in this shelf region. Overall, our study revealed the complex nature of POC cycling on this shelf, quantified the relative importance of each source of POC, and determined POC flux to the sediment.